2016
DOI: 10.24114/jtikp.v3i1.5001
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Pembelajaran Media Interaktif Pada Mata Pelajaran PPKN

Abstract: Abstrak: Penelitian ini bertujuan untuk: (1) menghasilkan media pembelajaran interaktif yang layak digunakan, mudah dipelajari dan dapat dipakai untuk pembelajaran individual (2) mengetahui efektifitas media pembelajaran interaktif Power Point yang dihasilkan, dalam meningkatkan hasil belajar pembelajaran PPKn. Produk akhir dari pengembangan media pembelajaran ini dilanjutkan dengan uji keefektifan produk. Metode yang digunakan dalam uji coba keefektifan produk adalah metode kuasi eksperimen. Sampel penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…b. Indonesian language learning media using Adobe Flash CS6 interactive media of news text material was higher than the Indonesian language learning outcomes without using Adobe Flash CS6 interactive media of news text material at the eighth grade of SMPN 5 of Tanjung Morawa in 2018/2019 academic year. These results indicated that the developed interactive multimedia can motivate students to explore the material [6]…”
Section: Resultsmentioning
confidence: 78%
“…b. Indonesian language learning media using Adobe Flash CS6 interactive media of news text material was higher than the Indonesian language learning outcomes without using Adobe Flash CS6 interactive media of news text material at the eighth grade of SMPN 5 of Tanjung Morawa in 2018/2019 academic year. These results indicated that the developed interactive multimedia can motivate students to explore the material [6]…”
Section: Resultsmentioning
confidence: 78%
“…Globalisasi mengarahkan perkembangan teknologi agar bermanfaat dalam proses pembelajaran demi meningkatkan mutu pendidikan. Teknologi informasi adalah hasil penerapan ilmu pengetahuan yang terorganisir secara sistematis untuk menyelesaikan permasalahan secara praktis menggunakan sistem informasi yang menggabungkan teknologi komputer dengan telekomunikasi (Budiman, 2017;Nurdyansyah et al, 2015 Pemanfaatan media dalam proses pembelajaran dimaknai bukan hanya sebagai penggunaan alat tetapi juga tentang proses memberikan rangsangan komunikasi sehingga terjadi proses belajar (Kurniawan & Saragih, 2016;Susilana & Riyana, 2009). Media pembelajaran menjadi objek pendukung kesuksesan proses pembelajaran yang ditunjukkan dengan tersampaikannya rangsangan dari pendidik ke peserta didik maupun sebaliknya (Ahern, 2016;Khairani & Febrinal, 2016).…”
Section: Pendahuluanunclassified
“…Civics is a learning process that can direct students to be responsible so that they can play an active role in society per the provisions of Pancasila (Astawa et al, 2020;Silvia et al, 2019). Students with good character will be able to show an attitude of responsibility in every action taken and pay attention to the interests of others (Kurniawan & Saragih, 2016). It shows that Civics learning plays an important role in nation-building.…”
Section: Introductionmentioning
confidence: 99%